2021
DOI: 10.52229/pbmj.v4i1.75
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Lack of Family Planning in Grand Multiparous Women

Abstract: Multiparity is a matter of great concern regarding the health of women as well as child. At the same time it has different determinants and socioeconomic backgrounds. Objective: To determine the determinants of lack of family planning in grand multiparous women. Methods: It is a descriptive cross sectional study including 271 GMP patients from DHQ Hospital Okara city. Mean age was 35 ± 10 years. Data was collected with the help of questionnaire and evaluated and analyzed using SPSS version 24. Mean and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Our findings align with previous research (32) that has consistently shown a link between lower educational level and socioeconomic status and increased risks of adverse perinatal outcomes. Studies (33,34) have demonstrated that higher educational attainment is associated with better health knowledge, healthier lifestyle choices, and increased utilization of prenatal care services. Women with higher education levels are more likely to have access to information about healthy pregnancy practices, understand the importance of prenatal care visits, and make informed decisions regarding their health and the health of their babies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with previous research (32) that has consistently shown a link between lower educational level and socioeconomic status and increased risks of adverse perinatal outcomes. Studies (33,34) have demonstrated that higher educational attainment is associated with better health knowledge, healthier lifestyle choices, and increased utilization of prenatal care services. Women with higher education levels are more likely to have access to information about healthy pregnancy practices, understand the importance of prenatal care visits, and make informed decisions regarding their health and the health of their babies.…”
Section: Discussionmentioning
confidence: 99%
“…There are two basic types of infertility including primary and secondary infertility. Infertility involved the genital organs of both males and females (John et al, 2022;Noor et al, 2021). Evaluation of infertility in females is necessary including uterotubal factor, ovulatory factor, and male factor (Carson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%